Extending the beach resort model : the case of Pattaya - Aw, Wen Ling (2009)
This research study seeks to understand the transformations in contemporary, large-scale beach resorts in Southeast Asia. Specifically, the study is conducted within the framework of Smith’s [1990] Beach Resort Model (BRM), and seeks to extend this eight-stage model. Pattaya is selected as the case study for this research.